Can meso-governments use metagovernance tools to tackle complex policy problems?. (1st July 2019) - Connell, Andrew; Martin, Steve; St Denny, Emily
Abstract : In recent years, a range of countries have devolved significant powers, responsibilities and funding to the regional level. This paper explores how and why the resulting meso-governments may use the tools of metagovernance. A detailed empirical analysis of homelessness policy in Wales found that skilful deployment of metagovernance tools enabled its meso-government to exploit the advantages of geographical and relational proximity to policy communities, while mitigating some of the constraints of its intermediate constitutional status, including limited formal powers and policy capacity. Junior government officials played multiple roles in homelessness networks, shaping and steering them through active network management while also participating in them. This 'governor-participant' role blurs the distinction made in the existing literature between 'hands-on' and 'hands-off' metagovernance tools. It also shows that, in the case of meso-governments at least, it is possible for low-ranking officials to exercise greater agency in policy development than has previously been assumed.